Pirate Tales. - Deary, Terry (Pirate Tales Ser., 2011)
Tom is a cabin boy for Captain Francis Drake, on his mission to stealSouth American gold from the Spanish fleet. Can Tom survive the tripround the world, through waves three times the height of their tinyship, help Drake defeat the Spanish galleons - and come back rich?